In vitro antimicrobial and anti-endotoxin action of Zingiber Officinale as auxiliary chemical and medicament combined to calcium hydroxide and chlorhexidine - Valera, Marcia Carneiro [UNESP]; Cardoso, Flávia Goulart Da Rosa [UNESP]; Maekawa, Lilian Eiko [UNESP]; Camargo, Carlos Henrique Ribeiro [UNESP]; De Oliveira, Luciane Dias [UNESP]; Carvalho, Cláudio Antônio Talge [UNESP] (MJS Publishing, Medical Journals Sweden AB, 2015)
Objective. This study was conducted in vitro to compare the effectiveness of Zingiber Officinale as an auxiliary chemical substance followed by placement of different intra-canal medication in removing endotoxins and cultivable micro-organisms from infected root canals. Materials and methods. Seventy-two root canals were contaminated with Enterococcus faecalis, Candida albicans and Escherichia coli for 28 days. After, the teeth were instrumented using Zingiber Officinale and divided into six groups according to the intra-canal medication: chlorhexidine gel; calcium hydroxide + chlorhexidine gel; glycolic ginger extract; calcium hydroxide + glycolic ginger extract; calcium hydroxide + saline solution and saline solution (control). Sample collections were performed after root canal contamination (Baseline; S1), after instrumentation (S2), 7 days after instrumentation (S3), after 14 days with intra-canal medication (S4) and 7 days after removal of intra-canal medication (S5). The results were analyzed by the Kruskal-Wallis and Dunn tests. Results. It was observed that in S2 and S3 there was significant reduction of the micro-organisms and the quantity of endotoxins after instrumentation. In samples S4 and S5 there was complete elimination of micro-organisms and significant reduction of endotoxins. Conclusion. It was concluded that Zingiber Officinale as an auxiliary chemical substance was effective on the micro-organisms tested, yet was unable to eliminate the endotoxins. Similarly, the intra-canal medication were effective on micro-organisms, yet did not completely eliminate the endotoxins.
Keywords: Endotoxins; Micro-organisms; Root canal irrigants; Root canal medicaments; Zingiber Officinale